Ancient Methods of Making Fire - Đuričić, Ljiljana (Balcanica - Annual of the Institute for Balkan Studies, 1997)
The oldest remains of fire date back approximately 1,000,000 years, and were discovered on Petralona site, Greece, and in Chou-Kou-Thien, China, from layers dated about 700,000 years ago. Other fire remains in Europe oflater date were found on the sites Torralba and Ambrona in Spain, Vertesszollos, Hungary, Terra Amata and L'Escale, France, and belong to the Mindel glaciation period (476.000 - 435.000 yrs).